Risk of Developing Periodontal Disease in Patients with Upper Respiratory Tract Allergy: A Retrospective Cohort Study - Chang, Nai-wen. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Periodontology.; Advisor: Wai Cheung.; Committee: Hugo Campos, Yau-Uua Yu, and Sarah Pagni.; Keywords: Dentistry, and Immunology.